2021
DOI: 10.20944/preprints202105.0552.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abnormal Liver Biochemistry Tests and Acute Liver Injury in COVID-19 Patients: Current Evidence and Potential Pathogenesis

Abstract: Globally, over the past several months millions of persons contracted the coronavirus disease 2019 (COVID-19) resulting in significant mortality. Health care systems are negatively impacted including the care of individuals with cancers and other chronic diseases such as chronic active hepatitis, cirrhosis and hepatocellular carcinoma. There are various probable pathogenic mechanisms that have been presented to account for liver injury in COVID-19 patients such as hepatotoxicity cause by therapeutic drugs, sev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 174 publications
1
8
0
1
Order By: Relevance
“…A similar finding was reported when comparing remdesivir with other treatments of COVID‐19: serum AST and ALT levels were significantly higher in the remdesivir group and the risk of hepatic impairment increased 46,47 . Some case studies suggested causality of hepatotoxicity as AST and ALT levels were elevated or peaked immediately after the initiation of remdesivir, but the situation ameliorated afterwards 22,48,49 . In addition, the disproportionately high reporting of aminotransferase elevation compared with other COVID‐19 treatment options suggested drug‐induced liver injury 50 …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A similar finding was reported when comparing remdesivir with other treatments of COVID‐19: serum AST and ALT levels were significantly higher in the remdesivir group and the risk of hepatic impairment increased 46,47 . Some case studies suggested causality of hepatotoxicity as AST and ALT levels were elevated or peaked immediately after the initiation of remdesivir, but the situation ameliorated afterwards 22,48,49 . In addition, the disproportionately high reporting of aminotransferase elevation compared with other COVID‐19 treatment options suggested drug‐induced liver injury 50 …”
Section: Discussionsupporting
confidence: 58%
“…46,47 Some case studies suggested causality of hepatotoxicity as AST and ALT levels were elevated or peaked immediately after the initiation of remdesivir, but the situation ameliorated afterwards. 22,48,49 In addition, the disproportionately high reporting of aminotransferase elevation compared with other COVID-19 treatment options suggested drug-induced liver injury. 50 Nonetheless, some studies did not associate remdesivir with liver injury as the difference of clinical measurements was insignificant between treatment and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, como se mencionó anteriormente, no está claro si el daño o disfunción hepática están relacionados con la infección viral directa o si es consecuencia del uso de fármacos potencialmente hepatotóxicos o parte de la disfunción multiorgánica [59]. La gamma glutamil transferasa (GGT), un biomarcador de diagnóstico para la lesión de los colangiocitos, también se ha informado que aumenta en los estudios de casos existentes de COVID-19 [61].…”
Section: Enzimas De Función Hepáticaunclassified
“…34 1.1.4 | Long-term effects on the liver during the path to recovery Elevated liver function tests have been reported with abnormal levels of aspartate aminotransferases (AST) and alanine aminotransferase (ALT). 36 Liver injury can also be related to drugs. Most patients with COVID-19 show mild liver damage and return to normal, targetted hepatoprotective therapy is necessary in patients with severe liver injury.…”
Section: Covid-19 Recovery: Long-term Side Effects and Lingering Symp...mentioning
confidence: 99%
“…Elevated liver function tests have been reported with abnormal levels of aspartate aminotransferases (AST) and alanine aminotransferase (ALT) 36 . Liver injury can also be related to drugs.…”
Section: Introductionmentioning
confidence: 99%